2018
DOI: 10.1194/jlr.m085431
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of a synthetic compared with a natural therapeutic pulmonary surfactant in adult mice

Abstract: Secreted pulmonary surfactant phosphatidylcholine (PC) has a complex intra-alveolar metabolism that involves uptake and recycling by alveolar type II epithelial cells, catabolism by alveolar macrophages, and loss up the bronchial tree. We compared the in vivo metabolism of animal-derived poractant alfa (Curosurf) and a synthetic surfactant (CHF5633) in adult male C57BL/6 mice. The mice were dosed intranasally with either surfactant (80 mg/kg body weight) containing universally 13C-labeled dipalmitoyl PC (DPPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The effect of the administration of exogenous surfactant on the synthesis and secretion of endogenous lung surfactant have been extensively studied, although the results are still controversial [2224]. In vivo studies suggested an enhanced synthesis of endogenous surfactant PC both in rabbits [25, 26] and preterm infants [27], while no noticeable effects on the endogenous synthesis have been described in mice treated with a therapeutic dose of both synthetic or natural exogenous surfactant [28]. In the present study, a clear dose-dependent tendency was observed for the comparison of the endogenous DSPC amount in the alveolar pool among the experimental groups, confirming a stimulation of endogenous DSPC secretion or synthesis after treatment, mainly when a therapeutic dose is administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the administration of exogenous surfactant on the synthesis and secretion of endogenous lung surfactant have been extensively studied, although the results are still controversial [2224]. In vivo studies suggested an enhanced synthesis of endogenous surfactant PC both in rabbits [25, 26] and preterm infants [27], while no noticeable effects on the endogenous synthesis have been described in mice treated with a therapeutic dose of both synthetic or natural exogenous surfactant [28]. In the present study, a clear dose-dependent tendency was observed for the comparison of the endogenous DSPC amount in the alveolar pool among the experimental groups, confirming a stimulation of endogenous DSPC secretion or synthesis after treatment, mainly when a therapeutic dose is administered.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot feasibility studies in preterm infants are ethically acceptable and they need to be done. Worth of note, in previous reports the contribution of newly synthesized surfactant has been estimated by the use of radio-labelled [24, 29] or stable isotope-labelled precursors of surfactant phospholipids [27, 28]. This is the first study in which the exogenous and endogenous surfactant can be distinguished in the alveolar pool without the need for administering any artificially labelled compound.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 64 Cu‐labeled antimicrobial peptoids when delivered systemically per oral, intravenously, or intraperitoneally generally exhibited higher in vivo stability and tissue accumulation and slower elimination in comparison to peptides . Although we expect that our peptoid mimics will be more resistant to protease degradation compared to peptides, further studies are needed to determine in vivo fate of the entire lipid‐peptoid complex; similar to a recent carbon 13‐labeled DPPC study comparing the in vivo metabolism of poractant alfa to a synthetic, peptide‐based surfactant, CHF5633 . Recently, a mono‐alkylated (single N ocd residue) variant of Mimic C was tested in an in vivo rat model of acute lung injury .…”
Section: Discussionmentioning
confidence: 84%
“…In vivo stable isotope animal studies showed a considerable delay in catabolism and enhanced phospholipid recycling of CHF5633 compared to poractant alfa. 38 Also, in vitro studies showed decreased proinflammatory cytokine synthesis in macrophages in response to CHF5633, 39 suggesting the possibility of better efficacy in preventing chronic lung disease in preterm infants with RDS and broader indications for surfactant replacement therapy, such as neonatal or pediatric ARDS. 40 Lambs treated with CHF5633 for RDS have better lung and brain injury scores than those treated with poractant alfa.…”
Section: Synthetic Surfactant Preparationsmentioning
confidence: 99%